The Impact of Business Ecosystem and Lifecycle on Start-up Creation Process – A Case Study of Indonesian Software Technology Start-ups - Febrianto Mulyawan; Wawan Dhewanto; Leo Aldianto (Jurnal Internasional Penelitian Bisnis Terapan, 2023)
Establishing start-ups with a higher level of maturity requires a higher level of techniques, methods, and tools. However, presently established start-ups still encounter difficulties in determining how to quantify their performance and resilience with knowledge of the start-up development process. This study intends to investigate and evaluate the features of the start-up ecosystem throughout its existence. It employed an in-depth case study through interviews and observations to better understand the start-up ecosystem and lifecycle of Indonesian software technology start-up companies. This study utilized a qualitative approach based on multiple explanatory case studies. By providing a conceptual understanding of eight fundamental elements of the start-up ecosystem and lifecycle processes, this study contributes to the identification and investigation of start-up enterprises. The findings provide insight into how to describe start-up enterprises through a multiple-case study. This study discovered that each stage of the start-up lifecycle has a distinct emphasis on improving the ecosystem in order to create a more resilient start-up company.